PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR SISWA MATERI KALOR SMA NEGERI 1 ANGKOLA TIMUR - Sari, Lia Purnama (Jurnal Physics Education (PhysEdu), 2023)
This study aims to determine the improvement of student physics learning outcomes in caloric material by using cooperative learning model TGT type. The population in this study are all students of class X in SMAN 1 Angkola Timur which amounts to 95 students. So the sample research used is the total sample. The research method used was quasi experiment with two pretest-posttest design studies. Researcher determine which become experiment class in this research is class X1 and control class in this research is class X3. Technique of collecting data using observation and test. While the data analysis using t-test. Based on the calculation, cooperative learning model type TGT meteri calor obtained an average value of 87.5% is in the category of "Very Good". The result of learning of caloric matter before using TGT type co-operative model got average value 60 is in "Enough" category, whereas learning result calor after using TGT type co-operative model obtained average. Value 80 is in the "Very Good" category. Through the calculation result at 95% confidence level or error rate 5% with degrees of freedom (dk) = 31. tcount> ttable (10.12>1.70). So it can be concluded that by using cooperative learning model type TGT can improve student learning outcomes calor with the category "Very Good".